A Checklist Instrument: Sensory Cues within Assisted Living Facilities - Wood-Nartker, Jeanneane; Beuschel, Emily; A. Guerin, Denise (Journal of Preventive Medicine And Care, 2017)
As people age, environments supporting changing needs can potentially impact their quality of life. The purpose of this exploratory study was to develop and assess the validity of a checklist instrument used to evaluate senior-supportive environmental risk factors within assisted living facilities (ALFs). Aging often leads to a decrease in the ability of a person to interpret sensory cues within his or her environment. This checklist instrument examined the relationship between sensory cue frequency and the influence on fall incidence within ALFs to maximize safety and quality of life. Observers visited 140 ALFs, utilizing the checklist instrument to document the presence or non-presence of 110 sensory cues. Contrary to the original hypothesis, a positive correlation was found between sensory cues and reported falls in each space. As the number of cues increased, the number of falls also increased. Additionally, the frequency of sensory cues within each room increased as facility size increased. Lastly, data revealed that more sensory cues were present in ALFs designed or renovated by design professionals. Although the results were contrary to expectations, the checklist instrument demonstrated face and predictive validity as a future research tool.
Keywords: Interior Design; Assisted Living Facilities; Long-term care facilities; Resident falls; Research instruments; Sensory cues